KELUARGA BERENCANA (KB) PERSPEKTIF Al-QUR’AN - Maskanah Maskanah (MUSHAF JOURNAL: Jurnal Ilmu Al Quran dan Hadis, 2024)
According to Islamic concepts, family is a united relationship between men and women through a marriage contract according to Islamic teachings. Mahmud Syaltut defines family planning as the regulation and spacing of births or efforts to prevent pregnancy temporarily or even permanently in connection with certain situations and conditions, both for the family concerned and in the interests of society and the state. Based on the Al-Qur'an, which is the main source of Islamic law, no Sharia text prohibits or orders family planning. This must be returned to the rules of Islamic law which state: "Basically everything and actions are permissible unless or until there are arguments that indicate their prohibition. This research aims to find out about family planning (KB) from the perspective of the Qur'an. The focus of this research is, what is family planning (KB)? What is family planning (KB) from the perspective of the Koran? What is the best birth spacing from the perspective of the Qur'an? This research is qualitative research using a library research approach, namely utilizing library sources to obtain data for the research. This research seeks to explore family planning (KB) from the perspective of the Koran and Hadith. In exploring matters related to this research, of course, using content analysis techniques. The results of this research are that if it is connected between Q.S. Al-Baqarah verse 233 with Q.S. Al-Ahqaf verse 15: From birth until two full years, mothers are commanded to breastfeed their children. Two years is the maximum limit for perfect breastfeeding. Although breastfeeding for two years is ordered, it is not an obligation. The breastfeeding period does not always have to be 24 months, because QS.al-Ahqaf verse 15 states that the pregnancy and breastfeeding period is 30 months. This means, if the fetus is carried for nine months, then breastfeeding is for 21 months, whereas if the fetus is only 6 months. So at that time breastfeeding was 24 months. Meanwhile, according to Masjfuk Zuhdi in his book Masail Fiqhiyyah, if we put these two verses together then at least 6 months of pregnancy and 24 months is the breastfeeding period. If we go back to habits, a mother's pregnancy is usually 9 months and 10 days. Thus, the pregnancy period plus the breastfeeding period is three years minus 3 months or once every 3 years. In this case, it is in line with the meaning contained in health science which states that mothers need time to maintain their health.